Literatur Review Vitamin D Terhadap Stres Oksidatif (MDA) - Ardila, Devi; Sripratiwi, Chessy; Paizer, Dindi; Nur Siddiq, Ahmad; Septa Prautami, Erike; Anggeria, Elis (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Vitamin D has many benefits and functions for body metabolism. The prevalence of vitamin D deficiency is still high in Indonesia. Vitamin D deficiency can improve inflammation and oxidative stress, and increase susceptibility to metabolic disorders and infections. Vitamin D deficiency is often associated with increased levels of malondialdehyde (MDA). Malondialdehyde (MDA), the end product of lipid peroxidation, functions as a reliable biomarker to assess the level of oxidative stress in vivo. The purpose of writing this literature review is to analyze the correlation of vitamin D levels with oxidative stress (MDA). Analysis of related literature was obtained from a search in the medical and health journal databases, namely PubMed-MEDLINE and Google Scholar and published in 2010-2025. 8 articles were obtained and included in this literature review. Based on the literature review, the correlation of vitamin D to oxidative stress (MDA) showed its effect. Vitamin D can reduce oxidative stress levels (MDA) in several diseases such as non-alcoholic liver disease, cystic fibrosis (CF), and certain cases such as obesity that can occur in the elderly and children.